The Effectiveness of Using Digital Marketing with the Intervening Variable of Human Resource Quality on Increasing the Number of Patients at the Permata Hati Bunda Clinic, Bekasi - Putri, Nabila Mazaya; Wahyudi, Bayu; Agung, Wiseto P. (Business Management, 2026)
This study aims to analyze the effectiveness of digital marketing in increasing the number of patients at Permata Hati Bunda Clinic, considering human resource (HR) quality as an intervening variable. A quantitative method with an explanatory research design was applied. The study involved 100 patients selected using consecutive sampling. Primary data were collected through a Likert-scale questionnaire, while secondary data were obtained from clinic patient records. Data analysis employed Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that digital marketing has a positive and significant effect on patient growth. Furthermore, HR quality significantly influences the effectiveness of digital marketing implementation. Another key finding reveals the mediating role of HR quality as a partial mediator that strengthens the impact of digital marketing on patient acquisition. Thus, the success of digital marketing strategies in clinics is not solely determined by content and digital platforms but also relies on staff competence, responsiveness, and professionalism in managing patient interactions. This research highlights that integrating digital marketing strategies with HR quality development is essential to enhance patient acquisition and build long-term loyalty.